1974
DOI: 10.1111/j.1432-1033.1974.tb03763.x
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribosyl Transfer Catalysis with trans‐N‐Deoxyribosylase

Abstract: Kinetic studies were carried out in order to investigate the enzymic mechanism of a 1420-fold purified purine nucleoside : purine deoxyribosyl transferase fraction from Lactobacillus helveticus. Deoxyinosine and adenine were used as substrates. Initial velocity, product inhibition and isotopic exchange studies are consistent with a ping-pong bi-bi mechanism (the first product is released before the second substrate combines with the enzyme). The numerical values of the Michaelis and dissociation constants, max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The cleavage reaction proceeds through an acyl enzyme intermediate in which an active site glutamate acts as the nucleophile [35,36]. Kinetic evaluation of the enzyme has revealed that nucleoside 2′-deoxyribosyltransferase utilizes a ping-pong kinetic mechanism [37].…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage reaction proceeds through an acyl enzyme intermediate in which an active site glutamate acts as the nucleophile [35,36]. Kinetic evaluation of the enzyme has revealed that nucleoside 2′-deoxyribosyltransferase utilizes a ping-pong kinetic mechanism [37].…”
Section: Discussionmentioning
confidence: 99%
“…A kinetic study [18] of trans-N-deoxyribosylase-I established a ping-pong mechanism in which the donor forms a first complex with the enzyme and the first product is released before the second substrate (acceptor) binds to the deoxyribosyl . enzyme.…”
Section: Quaternarj Structurementioning
confidence: 99%
“…NDTs from Lactobacillus helveticus and Lactobacillus leichmannii have been well studied (2,25,26,28,29), and their kinetic mechanisms as well as their catalytic and substrate binding sites have been characterized. The transferase reaction proceeds via a ping-pong bi-bi mechanism by formation of a covalent deoxyribosyl enzyme intermediate (3,15,16). Likewise, a glutamyl residue (Glu98) has been proven essential for activity (40,41,46).…”
mentioning
confidence: 99%